Predicting implementation of the PAX Good Behavior Game + MyTeachingPartner interventions - Braun, Summer S.; Bradshaw, Catherine P.; Beahm, Lydia A.; Budavari, Alexa C.; Downer, Jason; Ialongo, Nicholas S.; Tolan, Patrick H. (Frontiers in Psychology, 2023)
Introduction Effective classroom management is critical to creating a classroom environment in which social, emotional, and academic learning can take place. The present study investigated the association between early career, early elementary teachers’ occupational health (job stress, burnout, and perceived teaching ability) and perceptions of program feasibility in relation to their implementation dosage and quality of two evidence-based classroom management programs implemented together: the PAX Good Behavior Game (GBG) and MyTeachingPartner (MTP) intervention. Methods Teachers provided information on their occupational health at the start of the school year and were then randomized to the PAX GBG + MTP condition or control condition. Teachers’ perceptions of the feasibility of the program, implementation dosage, and implementation quality of the intervention were measured at the end of the school year for the 94 intervention teachers. Results Teachers participated in more MTP coaching cycles when they reported that the combined PAX GBG + MTP program was feasible. Although there were no main effects of occupational health on implementation, the associations between job stress and implementation quality were moderated by perceptions of feasibility. Discussion Findings highlight the complexity of factors influencing the implementation of evidence-based programs in school settings.